PANDANGAN AL-QUR`AN DAN AS-SUNNAH TENTANG WASATIYYAH (MODERASI) SERTA IMPLEMENTASINYA TERHADAP HUKUM ISLAM - Khoirun Nidhom (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2021)
The discussion of the Wasathiyyah Concept (Moderation) in the review of the Qur'an and Sunnah is a very urgent issue. Phenomenon that has occurred and developed in the global community, including Indonesia, to date when things are violent, radical and others, Muslims are always the victims. And what becomes very strange and ironic is that the perpetrators themselves are Muslims who do not understand the essence of the concept of wasathiyyah, especially in the field of Islamic law, which by chance this problem can be said that almost no one has studied it. Most scientists only study the concept of wasathiyyah in general. So from that this literacy tries to provide an understanding of the implementation of the wasatiyyah concept in the field of Islamic law. This research uses literary methods and literacy studies from classical and contemporary scholars who are experts in their fields. The results of this study definitely answer the implementation of the wasathiyyah concept in the field of Islamic law in accordance with the instructions of the Al-Qur`an and As-Sunnah.